Pengaruh Reward Terhadap Prestasi Belajar Siswa Di SD Swasta Al-Mutakinah - Firdaus, Randi; Kirana, Candra (Journal of Sustainable Education, 2025)
The purpose of this study was to determine the effect of giving rewards and the influence of rewards on students' learning interests at Al Mutakinah Private Elementary School, Imamah, Mandau District, Bengkalis Regency. This study used a qualitative approach with a descriptive research type. The qualitative approach was chosen because it aims to deeply understand the interests and learning outcomes of grade III students at Al Mutakinah Private Elementary School, Imamah, Mandau District, Bengkalis Regency. This approach also allows researchers to obtain richer and more detailed information through interviews, observations, and documentation that describe social reality naturally. This descriptive study focuses on describing students' conditions and how they affect their learning interests. Based on the results of the study on the effect of giving rewards on students' learning interests at Al Mutakinah Private Elementary School, Imamah, Mandau District, Bengkalis Regency, the following conclusions can be drawn: Planned and Varied Rewards, Rewards given by the school, such as certificates, medals, praise, and the opportunity to choose activities, have a positive influence on students' learning interests. This reward is one way to appreciate students' achievements and behavior, thus encouraging them to be more active in learning activities. Clear Reward Criteria Reward criteria that include academic achievement, positive attitudes, and student involvement in class activities, help students understand what the school expects. With these criteria, students are motivated to show their best efforts. The Right Time to Give Rewards Rewards that are given immediately after students reach their targets provide effective positive reinforcement. This increases students' learning motivation, because they feel that their efforts are directly appreciated. The Effect of Rewards on Learning Interests Giving rewards has been shown to increase students' learning interests. Students who receive rewards show higher enthusiasm in participating in learning activities, and strive to achieve better achievements in the future.